Flecainide induces a sustained countercurrent dependent effect on RyR2 in permeabilized WT ventricular myocytes but not in intact cells - Steer, Emma J.; Yang, Zhaokang; Al-Owais, Moza M.; Kirton, Hannah M.; White, Edward; Steele, Derek S. (Frontiers in Pharmacology, 2023)
While flecainide is now an accepted treatment for arrhythmias associated with catecholaminergic polymorphic ventricular tachycardia (CPVT), its mechanism of action remains controversial. In studies on myocytes from CPVT mice, inhibition of proarrhythmic Ca2+ waves was attributed to a novel action on the type-2 ryanodine receptor (RyR2). However, subsequent work on wild type (WT) myocytes questioned the conclusion that flecainide has a direct action on RyR2. In the present study, flecainide induced sustained changes Ca2+ sparks and waves in permeabilized adult rat ventricular myocytes (ARVM), which were comparable to those reported in intact or permeabilized myocytes from CPVT mice. However, a relatively high level of flecainide (25 µM) was required to induce these effects. In further experiments on permeabilized ARVM, inhibition of the SR counter-current was found to potentiate the effects of flecainide on SR Ca2+ release. In intact field stimulated ARVM, prolonged exposure to 15 µM flecainide decreased wave frequency but RyR2 dependent effects on Ca2+ sparks were absent; higher drug concentrations blocked field stimulation, consistent with inhibition of Nav1.5. In intact ARVM, the absence effects on Ca2+ sparks suggests that the intracellular flecainide concentration was insufficient to influence RyR2. Wave inhibition in intact ARVM may reflect secondary effects of Nav1.5 inhibition. Potentiation of flecainide’s action by counter-current inhibition can be explained if transient polarization of the SR membrane during Ca2+ release facilitates its action on RyR2.